ANGIOTENSIN II MODULATES MONOCYTE-TO-MACROPHAGE DIFFERENTIATION: EFFECT ON THP-1-LIKE MACROPHAGE CELL PHENOTYPE, POLARIZATION AND REACTIVE OXYGEN SPECIES GENERATION. (April 2021) - Barhoumi, Tlili; Boudjellal, Mohammad; Mahmud, Azra
Abstract : Objective: Circulating monocytes and tissue macrophages play complex roles in the pathogenesis of hypertension, a highly prevalent cardiovascular(CV) risk factor associated with increased CV morbidity and mortality. One of the main effector cells in innate immune response are macrophages and several studies have reported their implication in pathophysiology of hypertension. In the vasculature and kidney, macrophage-derived reactive oxygen species (ROS) and inflammatory cytokines cause endothelial dysfunction, resulting in vascular oxidative stress and impairment of sodium excretion. Furthermore, angiotensin (Ang) II infusion is known to induce hypertension and vascular damage, particularly endothelial dysfunction, inflammation and oxidative stress. Renin angiotensin system (RAS) stimulation triggers monocyte activation and migration. ROS and cytokines secreted by macrophages can modulate blood pressure(BP) by triggering vascular endothelial dysfunction. Angiotensin II receptors are expressed in immune cells like T cells and monocytes. The aim of our study was to explore the effect of angiotensin II on THP-1-like macrophage cell phenotype, polarization and ROS generation. Design and method: THP-1-like macrophage cells were incubated with Ang II (100 nM) for 48 h. Cell phenotype analysis was performed using flow cytometry after intracellular and extracellular staining with CD11c, CD64, CD206, HLA-DR, CD116 and TNFa. We determined the effect of Ang II stimulation on ROS generation by macrophages using Cell Rox kit; viability and apoptosis using immunofluorescence and cell phenotyping using flow cytometry. Results: There was a significant increase in ROS generation in cells incubated with Ang II compared with control. Ang II induces THP-1-like macrophage polarization by increasing HLA-DR, CD11c and TNFa and decreasing CD206 markers. Ang II significantly increases apoptosis in a time-dependent fashion from 24 to 72-h and changed cell CD inflammatory markers after 24-h incubation. Conclusions: Differences in ROS generation, phenotype and polarization of THP-1-like macrophage cells in presence of Ang-II may underlie the role of monocyte/macrophages in vascular inflammation. The downstream pathways may be a potential therapeutic target for ang-II induced inflammation and vascular damage in hypertension.